Mechanistic PKPD modeling to describe cytokine release associated with CD3 T-cell engager therapies - Lefèvre, Apolline; Parra-Guillen, Zinnia P.; Trocóniz, Iñaki F.; Boetsch, Christophe; Frances, Nicolas (Frontiers in Immunology, 2025)
IntroductionT-cell engagers (TCE), a therapeutic class of cancer immunotherapy (CIT), offer a novel approach to cancer treatment by harnessing and reactivating the patient’s immune system to eradicate tumor cells. However, the use of TCE in the clinic can lead to severe side effects, including cytokine release syndrome (CRS). Therefore, innovative dosing strategies need to be implemented to mitigate the risk of developing CRS.MethodIn the presented work, a mechanistic pharmacokinetics/pharmacodynamics (PKPD) model describing cytokine release following TCE therapy has been developed combining literature knowledge and preclinical data. The model was developed to explore and test hypotheses regarding the mechanisms behind the decrease of cytokine release following two repeated TCE administrations.ResultsThe model is able to successfully reproduce the observed dynamics of cytokine levels associated with the initial and subsequent TCE doses, accounting for different dosing intervals. In addition, the model suggests a mechanism of action that uncouples cytokine release from tumor cell killing.DiscussionThis model provides an initial mechanistic framework to support the design of experiments and paves the way for the application of mathematical modeling to support clinical dosing regimen selection of any TCE.